Community Pharmacy Operations in Puerto Rico During the 2017 Hurricane Season: A Descriptive Analysis of Rx Open Data. (9th December 2023) - Romolt, Courtney E.; Melin, Kyle; Hardie, Kinaya Y.; Baker, Sarah M.; Louissaint, Nicolette A.
Abstract: Objectives: This article aims to: (1) describe the 'Return to Open Pharmacy Operations' in Puerto Rico following the hurricanes Irma and Maria in the 2017 hurricane season, and (2) compare the recovery rate (Return to Open Pharmacy Operations) during the 2017 hurricane season between the US Commonwealth of Puerto Rico and the state of Florida. Methods: We performed a cross-sectional study of pharmacy operations in Puerto Rico utilizing Rx Open data for pharmacies in Puerto Rico during the 2017 hurricane season. To compare open rates of pharmacy operations over time in different contexts, we also analyzed Rx Open data for the state of Florida for Hurricane Irma. Results: Only 11.1% of pharmacies remained open in Puerto Rico 3 days after Hurricane Maria made landfall, and Puerto Rico pharmacy operations recovered slowly, at an average daily rate of 3.9% before reaching pre-landfall baseline operations. Puerto Rico pharmacy operations after Hurricane Maria recovered 10 times slower on average, compared to pharmacy operations in Florida after Hurricane Irma which reached baseline operations less than 1 week following Hurricane Irma's landfall. Conclusion: Our results demonstrate the unique severity of Hurricane Maria's impacts on Puerto Rico's health system.